Analysis and suppression of residual vibration in microhand for high-speed single-cell manipulation. (1st January 2013) - Avci, Ebubekir; Nguyen, Chanh-Nghiem; Ohara, Kenichi; Mae, Yasushi; Arai, Tatsuo
Stable grasping of micro-objects at high speed is a desired feature for micromanipulation systems. At high speed, however, the residual vibration tends to be greater. In this paper, we analyse the residual vibration of the end effector of the microhand during the high-speed grasping motion. Based on the analysis results, we propose suppression of residual vibration in two steps. First, the stiffness of the end effector is increased by structural design. Second, feedforward control is implemented since the behaviour of the vibration can predicted for the specific conditions. Preliminary experimental results show that the settling time decreases by 74% and the amplitude of the vibration by 47%.